Targeting delivery of simvastatin using ICAM-1 antibody-conjugated nanostructured lipid carriers for acute lung injury therapy. (1st January 2017) - Li, Shu-Juan; Wang, Xiao-Juan; Hu, Jing-Bo; Kang, Xu-Qi; Chen, Li; Xu, Xiao-Ling; Ying, Xiao-Ying; Jiang, Sai-Ping; Du, Yong-Zhong
Abstract: Acute lung injury (ALI) is a critical illness without effective therapeutic modalities currently. Recent studies indicated potential efficacy of statins for ALI, while high-dose statins was suggested to be significant for attenuating inflammation in vivo . Therefore, a lung-targeted drug delivery system (DDS) delivering simvastatin (SV) for ALI therapy was developed, attempting to improve the disease with a decreased dose and minimize potential adverse effects. SV-loaded nanostructured lipid carriers (SV/NLCs) with different size were prepared primarily. With particle size increasing from 143.7 nm to 337.8 nm, SV/NLCs showed increasing drug-encapsulated efficiency from 66.70% to 91.04%. Although larger SV/NLCs exhibited slower in vitro cellular uptake by human vascular endothelial cell line EAhy926 at initial stage, while in vivo distribution demonstrated higher pulmonary accumulation of the larger ones. Thus, the largest size SV/NLCs (337.8 nm) were conjugated with intercellular adhesion molecule 1 (ICAM-1) antibody (anti-ICAM/SV/NLCs) for lung-targeted study. The anti-ICAM/SV/NLCs exhibited ideal lung-targeted characteristic in lipopolysaccharide-induced ALI mice. In vivo i.v. administration of anti-ICAM/SV/NLCs attenuated TNF-α, IL-6 and inflammatory cells infiltration more effectively than free SV or non-targeted SV/NLCs after 48-h administration. Significant histological improvements by anti-ICAM/SV/NLCs were further revealed by H&E stain. Therefore, ICAM-1 antibody-conjugated NLCs may represent a potential lung-targeted DDS contributing to ALI therapy by statins.